Níveis e épocas de desfolha artificial no desempenho agronômico da cultura da mandioca - Ecco, Martios (2015)
Cassava roots are dependent on the leaves for the production of assimilates to be converted into sugars and accumulated in roots and starch. The artificial defoliation in economic importance of culture becomes a useful methodology to simulate damage of defoliating pests and also by climatic conditions (hail). This study aimed to evaluate the agronomic performance of the cassava crop in terms of times and levels of artificial defoliation. The experiment was conducted in Guaira, PR municipality in a Oxisol clayey. The experimental design was randomized blocks in a factorial 5 x 5, 5 levels of defoliation and 5 times of artificial defoliation, with 3 repetitions. The levels consisted of 0, 25, 50, 75 and 100% defoliation, performed with the aid of scissors cutting the proper proportions of all the leaves of the plant at different times of culture development. The leafless were performed at 45, 90, 135, 180 and 225 days after planting and after the sprouting of the branches of the first cycle. It was found that the behavior of the variables plant height and stem diameter were similar in the two cycles of development through interaction levels factors and times of defoliation, while the number of leaves, there was an increase when the plant was completely defoliated during the second cycle in the 90 and 135 DAB because it provided the largest branch of the stem, however, did not contribute to variations in shoot mass and starch accumulation in roots. The size of the roots (length and diameter) just were affected by treatments and the number of roots per plant despite having significant effect when subjected to treatment in the second crop cycle, was deteriorating same due possibly by environmental conditions and by genetic characteristics of the material and not the applied treatments. The most drastic defoliation (75 and 100%) when applied at 132 days after planting obtained an output of 33874 kg ha-1 sufficient to reduce the mass of roots intensively plant, while for the deposition of starch (starch ) the tuberous roots only levels had a significant effect to reduce their accumulated amount, with generally linear effect according to the increased defoliation. It can be concluded that the leafless cassava plant at 45 days after planting or after sprouting can recover from defoliation damage and the levels and times of defoliation, little interfere with root size and the number of roots plant was not influenced by defoliation at different levels or at different times, however, defoliation between 122 and 132 days after planting and stem sprouting, resulting in greater damage to root mass. As for the qualitative aspect, the most drastic defoliation levels (75 and 100%) cause the greatest losses in the amount of starch stored in independent storage roots of defoliation season.